Trend dan Tantangan Manajemen Kurikulum Pendidikan Islam - Ayu Amalia Insani; Nada Hamdi Elsawaf; Failasuf Fadli; Mochamad Iskarim (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Islamic education has an important role in shaping the character and morals of Muslim individuals. Curriculum management in Islamic education faces various trends and challenges that need to be understood and overcome to improve the quality of education. This article uses a literature review approach to analyze trends and challenges in Islamic education curriculum management. The literature sources used include books, journals and articles related to Islamic education curriculum management. The purpose of this article is to present a clear picture of trends and challenges in Islamic education curriculum management and provide recommendations for overcoming these challenges. Various trends in Islamic education curriculum management include the integration of technology in learning, improving teacher quality, and developing competency-based curricula. Challenges faced include lack of resources, changing educational policies, and resistance to change. To overcome the challenges faced in Islamic education curriculum management, steps are needed such as increasing investment in teacher training, updating the curriculum according to current developments, and using technology in teaching. Apart from that, cooperation between educational institutions, government and society is also needed to create a conducive educational environment.